2021
DOI: 10.1371/journal.pone.0258594
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular species delimitation of shrub frogs of the genus Pseudophilautus (Anura, Rhacophoridae)

Abstract: Sri Lanka is an amphibian hotspot of global significance. Its anuran fauna is dominated by the shrub frogs of the genus Pseudophilautus. Except for one small clade of four species in Peninsular India, these cool-wet adapted frogs, numbering some 59 extant species, are distributed mainly across the montane and lowland rain forests of the island. With species described primarily by morphological means, the diversification has never yet been subjected to a molecular species delimitation analysis, a procedure now … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Furthermore, our best fitted diversification models (Table 2) also support non-constant extinction rates on the diversification, confirming that extinctions played a major role in rhacophorid diversification. In fact, rhacophorids are known to have the highest number of extinct species among anuran families (Meegaskumbura et al, 2007;IUCN, 2012;Ellepola et al, 2021). Although the explanation of the origin of rhacophorids that suggest an alternative direct land connection between Madagascar and East/ Southeast Asia is also plausible, but this is yet to be supported with fossil evidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our best fitted diversification models (Table 2) also support non-constant extinction rates on the diversification, confirming that extinctions played a major role in rhacophorid diversification. In fact, rhacophorids are known to have the highest number of extinct species among anuran families (Meegaskumbura et al, 2007;IUCN, 2012;Ellepola et al, 2021). Although the explanation of the origin of rhacophorids that suggest an alternative direct land connection between Madagascar and East/ Southeast Asia is also plausible, but this is yet to be supported with fossil evidence.…”
Section: Discussionmentioning
confidence: 99%
“…This shows that paleo-climates had a significant impact on their diversification. Despite the fact that it has been suggested that the Asian monsoons, which formed with the beginning of the Himalayan-Tibetan orogeny, affected their diversification (Li et al, 2013;Vijayakumar et al, 2016;Meegaskumbura et al, 2019;Chen et al, 2020;Ellepola et al, 2021), this idea had not been empirically demonstrated. Here, using a complete time calibrated phylogeny we investigate the biogeograp hica l o rigin a nd evolu t ionary history o f Rhacophoridae.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 112 frog species recorded in Sri Lanka (Ellepola et al, 2021), the 93 extant species were considered in this study. The 18 extinct species were discounted as their distributional ranges have not been well documented (de Silva, Ukuwela & Chathuranga, 2022), whereas Hoplobatrachus tigerinus was discounted as its occurrence is now refuted (Dutta, 1997; Batuwita et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Sri Lanka has been separated from India for approximately 10,000 years (Pethiyagoda & Sudasinghe, 2021), and the speciation of amphibians has resulted in 86% endemism in frog species and 25% endemism in frog genera. Home to 112 species of amphibians (Ellepola et al, 2021), the species richness in the country, during recent times, has led to studies that describe multiple species at a time (Meegaskumbura, Manamendra‐Arachchi & Pethiyagoda, 2009; Wickramasinghe et al, 2013b). The remarkably high endemism within the island has led some authors to raise concern over considering Sri Lanka and the Western Ghats as a single biodiversity entity (Bossuyt et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…[21](AmphibiaWeb, 2023) out of which three (P. wynaadensis, P. amboli and P. kani) represent a subclade from India. The Sri Lankan diversification comprise of 16 extinct species [33] (Meegaskumbura et al 2007) as well as 10 nominal species lacking genetic data [55] (Ellepola et al 2021). We included 41 species of Sri Lankan Pseudophilautus, whose validity has been confirmed based on the general lineage concept [56](de Quiroz, 1999), in the current analysis.…”
Section: Methodsmentioning
confidence: 99%